The role of environmental factors in autoimmune thyroiditis - Hybenova, Monika; Hrda, Pavlina; Procházková, Jarmila; Stejskal, Vera; Sterzl, Ivan (Neuro-endocrinology letters, 2010)
Environmental factors can play an important role in the development of autoimmune thyroiditis (AT) and other autoimmune diseases. This article reviews the role of heavy metals and infectious agents in AT. Currently, the genes responsible for a metal-induced pathology are known in experimental animals but similar knowledge is lacking in man. Metals such as nickel or mercury induce delayed type T cell hypersensitivity (allergy) which is relatively common, especially in women. T-cell allergy can be studied with the lymphocyte transformation test, LTT-MELISA. It has been found that patients with AT and other autoimmune diseases, such as multiple sclerosis, psoriasis, systemic lupus erythematosus and atopic eczema, show increased lymphocyte reactivity in vitro to inorganic mercury, nickel and other metals compared to healthy controls. The important source of mercury is dental amalgam. Replacement of amalgam in mercury-allergic subjects resulted in improvement of health in about 70% of patients. Several laboratory parameters such as mercury-specific lymphocyte responses in vitro and anti-thyroid autoantibodies were normalized as well. In contrast, no changes in health and laboratory results were observed in mercury-allergic patients who did not have their amalgams replaced. The same was true for non-allergic patients who underwent amalgam replacement. Infectious agents such as Helicobacter pylori (Hp) may cause chronic inflammation and autoimmune reactivity in susceptible subjects. The results of in vitro experiments performed with lymphocytes from Hp infected patients indicate that Hp can cause immunosuppression which might be eliminated by successful eradication therapy. In conclusion, heavy metals and Hp infection may play an important role in AT. Laboratory tests, such as LTT-MELISA, can help to determine the specific etiological agents causing inflammation in individual patients. The treatment of AT and other autoimmune diseases might be improved if such agents are eliminated and any future exposure restricted.
Keywords: aktivace lymfocytů; Environmental Exposure; Helicobacter pylori; zánět; Lymphocyte Activation; zubní amalgam; Metals, Heavy; lidé; Inflammation; Thyroiditis, Autoimmune; autoimunitní tyreoiditida; Humans; Dental Amalgam; vystavení vlivu životního prostředí; těžké kovy